2007
DOI: 10.1007/s11255-006-9096-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure in a patient with severe hemolysis

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a clonal disorder of bone marrow. It is characterized by blood cells lacking membrane proteins that are normally attached by the glycosylphosphatidylinositol (GPI) anchor. The cellular defect arises in a hematopoetic stem cell and is due to somatic mutation of the Phosphatidylinositol-glycan protein-A gene (PIG-A gene), encoding a protein needed for the biosynthesis of the anchor GPI. Paroxysmal nocturnal hemoglobinuria is presented by intravascular hemolysis, cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…Among them, three patients subsequently developed CKD (chronic glomerular filtration rate (GFR) < 60 ml/minute/1.73 m 2 ). Similar studies have reported AKI as the first clinical sign in PNH in a total of five patients [11][12][13][14]. Interestingly, two of those patients presented with repeated episodes of AKI in combination with hemolytic anemia, not previously investigated.…”
Section: Clinical Features Of Kidney Injurysupporting
confidence: 70%
See 2 more Smart Citations
“…Among them, three patients subsequently developed CKD (chronic glomerular filtration rate (GFR) < 60 ml/minute/1.73 m 2 ). Similar studies have reported AKI as the first clinical sign in PNH in a total of five patients [11][12][13][14]. Interestingly, two of those patients presented with repeated episodes of AKI in combination with hemolytic anemia, not previously investigated.…”
Section: Clinical Features Of Kidney Injurysupporting
confidence: 70%
“…When renal biopsies are performed in PNH patients presented with kidney injury, among the typical findings are hemosiderin deposits in tubular cells, most prominent in the proximal tubules. Interestingly, no evidence of renal arterial or vein thrombosis has been presented in relevant case reports or in larger studies conducted in PNH patients treated with eculizumab [11][12][13][14][15][16][17][18]20]. However, the possibility that subclinical microvascular thrombosis could contribute to renal dysfunction cannot be excluded [21].…”
Section: Clinical Features Of Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…11 To our knowledge, two reports indicated that MRI was helpful in confirming the diagnosis of AKI secondary to PNH. 3,12 Features typical of renal cortical hemosiderosis were found in our patient, suggesting that her kidney injury was, at least in part, caused by PNH. Table 2 summarizes the reported cases of AKI secondary to PNH.…”
Section: Discussionsupporting
confidence: 51%
“…As a noninvasive alternative examination, MRI provides evidence of the renal cortical hemosiderosis characteristic of PNH, including reversed renal cortex‐medulla differentiation on T1 weighted images and a substantial loss of cortical signal intensity on both T1 and T2 weighted images . To our knowledge, two reports indicated that MRI was helpful in confirming the diagnosis of AKI secondary to PNH . Features typical of renal cortical hemosiderosis were found in our patient, suggesting that her kidney injury was, at least in part, caused by PNH.…”
Section: Discussionsupporting
confidence: 49%